Case report of connubial frontal fibrosing alopecia - Da Silva Libório, Ricardo [UNESP]; Trüeb, Ralph (Wolters Kluwer, 2018)
Since its original report in 1994, frontal fibrosing alopecia has become increasingly common, attracting the attention of the medical community and giving rise to speculations on its etiology, specifically the possibility of environmental factors. Familial cases of frontal fibrosing alopecia point to the possible contribution of hereditary factors maybe related to androgenetic alopecia. We report the first case of connubial frontal fibrosing alopecia in a genetically unrelated couple pointing to the possibility of a common environmental exposure in the etiology of the condition. Our observation may be fortuitous, considering the high frequency of female frontal fibrosing alopecia. Nevertheless, the incidence of male frontal fibrosing alopecia has remained low with a consequently low statistical probability of random occurrence of the condition in a marital couple. We, therefore, suggest to systematically includes the hair condition of marital partners in the patient history of patients with frontal fibrosing alopecia, to elucidate the actual frequency of connubial frontal fibrosing alopecia and maybe a common causative agent or hair grooming practice.
Keywords: Causative environmental agent or grooming practice; connubial frontal fibrosing alopecia; female frontal fibrosing alopecia; male frontal fibrosing alopecia